Preference for Mathematics Textbook Illustrations among Primary School Pupils in Ibadan: Implications for Counselling Psychology - Kamilu Olanrewaju, Dr. Muraina (International Journal of Educational Development in Africa)
The purpose of this study was to investigate the preference among primary school pupils in Ibadan in terms of mathematics textbook illustrations and its implications for counselling psychology. An ex post facto descriptive research design was used in the study. One hundred and three (103) respondents were selected from public primary school pupils in Ibadan, Oyo State, Nigeria. The respondents were measured with self-developed scales and the data obtained was analysed using the Pearson Product Moment Correlation Coefficient (PPMC) and Statistical Package for the Social Sciences (SPSS) software. Two (2) research questions were raised and answered in the study. The results show that there is a significant relationship between paper quality and preference for mathematics textbook illustrations (r = .712; P<0.05), and there was a significant relationship between colours used in the book and mathematics textbook illustration preferences (r = .841; P<0.05). In view of these findings, the study stresses that educational stakeholders and counsellors should intensify their effort to organise conferences on the implications of these factors (e.g., colour and paper quality, among others) relating to the pupils’ preferences for textbooks, which invariably affect reading comprehension of the pupils.